Effect of Nigella sativa oil supplement on risk factors for cardiovascular diseases in patients with type 2 diabetes mellitus. (8th June 2020) - Kooshki, Akram; Tofighiyan, Tahereh; Rastgoo, Neda; Rakhshani, Mohammad Hassan; Miri, Mohammad
Abstract: This study aimed to evaluate the effects of Nigella sativa oil on serum level of systemic inflammation, oxidative stress, fasting blood glucose (FBG), and lipid profile in patients with type 2 diabetes mellitus (T2DM). This double‐blind randomized clinical trial study was based on 50 patients with T2DM. Patients were allocated randomly to either N. sativa oil or placebo groups. The intervention group received 1, 000 mg N. sativa oil as two capsules, daily for 8 weeks, whereas the placebo group received a corresponding placebo. At baseline and the end of the study, 5 ml blood was collected from each patient after 14‐hour fasting for measuring serum C‐reactive protein (hs‐CRP), malondialdehyde (MDA), FBS, and lipid profile. Analyses covariance was performed to compare investigated parameters between two groups, controlled for relevant covariates. Using N. sativa supplement was significantly associated with decrease in FBS ( p < .001), triglyceride ( p < .001), total cholesterol ( p < .001), low‐density lipoprotein cholesterol ( p < .001), serum hs‐CRP, MDA ( p < .001) and increase in serum level of high‐density lipoprotein cholesterol ( p < .001) in intervention group compared with placebo group. Nigella sativa oil supplement has cardiovascular protective effects in patients with T2DM, by improving the lipid profile and glycemia, by reducing the C‐reactive protein level and the lipid peroxidation.